Some Generalized Difference Sequence Spaces Over Bi-complex Scalars (Journal of Institute of Science and Technology, 2025)
In this article, we have introduced the notion of generalized difference sequence spaces within the framework of bi-complex numbers. Further we have established their algebraic, topological and geometric properties including some inclusion relations.